Three Decades of Research on Individual Teacher-Child Relationships: A Chronological Review of Prominent Attachment-Based Themes - Spilt, Jantine L.; Koomen, Helma M. Y. (Frontiers in Education, 2022)
Attachment theory has played a prominent role in the study of affective relationships between teachers and individual children in school settings. This review synthesizes three decades of attachment-based research on teacher-child relationships roughly covering the period between 1992 and 2022. Five key themes were discussed: 1) conceptualization and assessment, 2) secure base and autonomous exploration, 3) safe haven and self-regulation, 4) attachment history and relationship (dis)continuity, and 5) teacher sensitivity and mentalization. Following a narrative review approach, a selection of pivotal research studies was made and chronologically presented to illustrate research developments per theme. The results indicated that the conceptualization and assessment of teacher-child relationships holds largely, but not completely, across different developmental phases, cultural contexts, measurement methods, and informants. In addition, research confirmed the role of the secure base and safe haven functions of teacher-child relationships in promoting children’s emotional security at school. Furthermore, progression has been made through the development of multiple measurement methods for both teachers and children, by expanding research from early childhood education up to secondary education, and by more recent cross-cultural studies. However, there is still limited insight in mechanisms that explain (dis)continuity in relationships over time, and a striking lack of research on dyadic teacher sensitivity and mentalization as antecedents of teacher-child relationships. Research directions for the following decade(s) of research are provided per theme.